The Baltic Crusades and ecological transformation: The zooarchaeology of conquest and cultural change in the Eastern Baltic in the second millennium AD. (20th March 2019) - Pluskowski, Aleksander; Makowiecki, Daniel; Maltby, Mark; Rannamäe, Eve; Lõugas, Lembi; Maldre, Liina; Daugnora, Linas; Black, Stuart; Müldner, Gundula; Seetah, Krish
Abstract: From the end of the 12th century, crusading armies unleashed a relentless holy war against the indigenous pagan societies in the Eastern Baltic region. Native territories were reorganised as new Christian states (Livonia and Prussia) largely run by a militarised theocracy, dominated by the Teutonic Order. The new regime constructed castles, encouraged colonists, developed towns and introduced Christianity, incorporating the conquered territories into Latin Europe. At the same time, the theocracy sought to maximise the exploitation of natural resources to sustain its political and military assets, as well as provision its subjects. Arguably the most important resource was represented by animals, which were exploited for a range of primary and secondary products. Excavations across the eastern Baltic have uncovered tens of thousands of faunal remains from archaeological contexts on either side of the crusading period. Traditionally studied in isolation, the zooarchaeological data is here for the first time compared across the conquered territories, supported with isotopic analyses and integrated with other paleoenvironmental and historical sources, revealing how the new regime appropriated and intensified existing livestock husbandry practices, whilst accentuating earlier trends in declining biodiversity. At the same time, agricultural changes led to improved feeding regimes, resulting in noticeable changes in the size of stock in some regions.